2010
DOI: 10.1161/hypertensionaha.110.154567
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibition Attenuates Inflammatory, Hypertrophic, and Hypertensive Responses in Spontaneously Hypertensive Rats

Abstract: Abstract-Reactive oxygen species and proinflammatory cytokines contribute to cardiovascular diseases. Inhibition of downstream transcription factors and gene modifiers of these components are key mediators of hypertensive response. Histone acetylases/deacetylases can modulate the gene expression of these hypertrophic and hypertensive components. Therefore, we hypothesized that long-term inhibition of histone deacetylase with valproic acid might attenuate hypertrophic and hypertensive responses by modulating re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 46 publications
5
152
1
Order By: Relevance
“…9 The anti-inflammatory effects of PPAR-␤ could be related to the blood pressure-lowering effect. However, additional mechanisms must be involved, because antihypertensive drugs like hydralazine do not reduce proinflammatory cytokines, 35 and PPAR␤ agonists also exert anti-inflammatory effects in vitro as well. 20 Vascular microarray profiling in 2 models of hypertension, including SHRs, identified caveolin 1, RGS2, and RGS5 as key antihypertensive targets.…”
Section: Discussionmentioning
confidence: 99%
“…9 The anti-inflammatory effects of PPAR-␤ could be related to the blood pressure-lowering effect. However, additional mechanisms must be involved, because antihypertensive drugs like hydralazine do not reduce proinflammatory cytokines, 35 and PPAR␤ agonists also exert anti-inflammatory effects in vitro as well. 20 Vascular microarray profiling in 2 models of hypertension, including SHRs, identified caveolin 1, RGS2, and RGS5 as key antihypertensive targets.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be more specific to HDAC1, -2, or -3, as the more selective class I HDAC inhibitor apicidin suppresses cardiac hypertrophy and improves function in a mouse model of pressure overload (131). HDAC inhibitors also reduce fibrosis and negative remodeling of the heart after myocardial infarction injury in the rat, as well as in rat models of spontaneous and salt-sensitive hypertension (132)(133)(134). These results are consistent with genetic studies in Hdac2-null mice, which show less cardiac hypertrophy induced by various pathologic stimuli (135).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…A recent study clarified that the class I and IIa HDACs play critical roles in mediating cardiac hypertrophy. For example, HDAC2 was activated by hypertrophic stresses in association with the induction of heat shock protein 70 (17), mice lacking HDAC5 and/or HDAC9 exhibited exacerbated cardiac hypertrophy in response to stress induced by aortic stenosis (26,27), an inhibitor of class I HDACs valproic acid attenuated cardiac hypertrophy in SHR (5). On the other hand, it was reported that HDAC4 is predominantly associated with muscle and chondrocyte development (28,50).…”
mentioning
confidence: 99%